Transvaginal sonographic monitoring of the uterine effects of raloxifene and a continuous combined replacement therapy in postmenopausal women - Christodoulacos, G.; Panoulis, C.; Botsis, D.; Rizos, D.; Kassanos, D.; Creatsas, G. (Maturitas, 2002)
Objective: To study the effect of 17β-estradiol+norethisterone acetate and raloxifene on the endometrium and uterine volume in postmenopausal women. Methods: Patients were randomly assigned to 17β-estradiol 2 mg+norethisterone acetate 1mg (E2+NETA) daily (n=90) or raloxifene HCl 60 mg (Evista) daily (n=43). Transvaginal sonography was done at baseline and at 6, 12 and 18 months, and at 6 and 12 months in-patients treated with E2+NETA and EVISTA respectively. Patients were asked to record bleeding-spotting episodes. Whenever required patients were referred for hysteroscopy±biopsy of the endometrium. Results: Patients under E2+NETA had a higher bleeding-spotting incidence (48.6%) compared with EVISTA (7.7%). Endometrial thickness increased significantly under E2+NETA as compared with baseline; however, at end point thickness reverted to baseline values. Evista had a non-stimulatory effect on the endometrium. Changes in uterine volume were not statistically significant. Conclusions: Both treatment regimens provided comparable uterine safety. However, raloxifene exhibited a more favorable safety profile on the uterus as expressed in the bleeding-spotting incidence and the effect on endometrial thickness and uterine volume. Transvaginal sonography appears to be a dependable method for monitoring the effect of treatment on the uterus. © 2002 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: HRT; raloxifene; Sonography; Transvaginal sonographic monitoring